Enhancing Pedagogical Approaches for Fostering Patriotism In Students During Educational Transformation - Sadiev, Valijon (Indonesian Journal Publisher, 2024)
Developing patriotic qualities in students is essential for fostering a strong national identity and civic responsibility, especially in times of social and educational transformation. This article explores effective approaches to improve pedagogical conditions for instilling patriotism in educational settings. It highlights strategies including curriculum innovations, experiential learning, and the integration of inclusive teaching practices. The analysis draws on recent research findings to present evidence-based methods for enhancing patriotic education.